2013
DOI: 10.1002/etc.2396
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the laboratory culture of the fathead minnow, Pimephales promelas

Abstract: Fathead minnows are routinely cultured for use in aquatic toxicology studies. A new mass culture system described in the present study consisted of 6 stainless steel tanks, each containing 68 fish and 20 spawning substrates. Spawning results are compared with a previous system of 22 individual glass aquaria, which contained 16 fish and 4 spawning substrates per tank. During a 19-mo period, the new system produced an average of 4105 eggs/d, compared with an average of 2465 eggs/d with the previous system. Labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Once test fish reached maturity, spawning was initially intermittent and only increased as of Days 254 and 256 in the two trials. The trials started in October and December, thus this increase in egg production occurred in April to May, corresponding to the time of natural reproduction and possibly reflecting seasonality in fecundity in the laboratory, as seen by Gordon et al (). Direct comparison of fecundity data from Thurston et al () with other studies is not possible, as reported fecundity was based on total egg production divided by the total age of each female, rather than spawning duration.…”
Section: Water Qualitymentioning
confidence: 81%
See 4 more Smart Citations
“…Once test fish reached maturity, spawning was initially intermittent and only increased as of Days 254 and 256 in the two trials. The trials started in October and December, thus this increase in egg production occurred in April to May, corresponding to the time of natural reproduction and possibly reflecting seasonality in fecundity in the laboratory, as seen by Gordon et al (). Direct comparison of fecundity data from Thurston et al () with other studies is not possible, as reported fecundity was based on total egg production divided by the total age of each female, rather than spawning duration.…”
Section: Water Qualitymentioning
confidence: 81%
“…The standard protocol for evaluating the effects of potential toxins on the reproduction of fathead minnows called for a 2:1 sex ratio, with four females to two males per replicate tank (Ankley, Jensen, Kahl, Korte, & Makynen, ). In large tanks with 68 fish, a ratio of 8 males to 60 females optimized egg production (Gordon et al, ). Roush et al () considered that the best sex ratio to produce even‐aged fathead minnow embryos for testing purposes was four females to one male.…”
Section: Sex Ratiomentioning
confidence: 99%
See 3 more Smart Citations